Beyond the teacher-student model - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
A participatory approach. One way to get to know the needs of a group is for the extension worker to show several typical photos to the group, such as a good field of groundnuts, a farmer with a donkey, some faces. Each member of the group selects...